Developmental stage and morphology of the competent blastocyst are associated with sex of the child but not with other obstetric outcomes: a multicenter cohort study. Issue 1 (19th November 2021) - Borgstrøm, M B; Kesmodel, U S; Klausen, T W; Danielsen, A K; Thomsen, T; Gabrielsen, A; Englund, A L M; Zedeler, A; Povlsen, B B; Troest, B; Almind, G J; Fedder, J; et al.
Abstract: STUDY QUESTION: Are transfer day, developmental stage and morphology of the competent blastocyst in pregnancies leading to live birth associated with preterm birth, birthweight, length at birth and sex of the child? SUMMARY ANSWER: A high score in blastocyst developmental stage and in trophectoderm (TE) showed a significant association with the sex of the child, while no other associations with obstetric outcomes were observed. WHAT IS KNOWN ALREADY: The association between blastocyst assessment scores and obstetric outcomes have been reported in small single-center studies and the results are conflicting. STUDY DESIGN, SIZE, DURATION: Multicenter historical cohort study based on exposure data (transfer day (blastocyst developmental stage reached by Day 5 or Day 6)) blastocyst developmental stage (1–6) and morphology (TE and inner cell mass (ICM): A, B, C)) and outcome data (preterm birth, birthweight, length at birth, and sex of the child) from women undergoing single blastocyst transfer resulting in a singleton pregnancy and live birth. PARTICIPANTS/MATERIALS, SETTING, METHODS: Data from 16 private and university-based facilities for clinical services and research were used. A total of 7246 women, who in 2014–2018 underwent fresh-embryo transfer with a single blastocyst or frozen-thawed embryo transfer (FET) with a single blastocyst resulting in a singleton pregnancy were identified. Linking to the Danish Medical Birth Registry resulted in a total of 4842 women with a live birth being included. Cycles with pre-implantation genetic testing and donated gametes were excluded. The analyses were adjusted for female age (n = 4842), female BMI (n = 4302), female smoking (n = 4290), parity (n = 4365), infertility diagnosis (n = 4765), type of treatment (n = 4842) and center (n = 4842); some analyses additionally included gestational age (n = 4368) and sex of the child (n = 4833). MAIN RESULTS AND THE ROLE OF CHANCE: No statistically significant associations between blastocyst assessment scores (transfer day, developmental stage, TE, ICM) and preterm birth (8.3%) or birthweight (mean 3461.7 g) were found. The adjusted association between blastocysts with a TE score of C and a TE score of A and length at birth (mean 51.6 cm) were statistically significant (adjusted mean difference 0.4 cm (95% CI: 0.02; 0.77)). Blastocysts transferred with developmental stage score 5 compared to blastocysts transferred with score 3 had a 34% increased probability of being a boy (odds ratio (OR) 1.34 (95% CI: 1.09; 1.64). Further, TE score B blastocysts compared to TE score A blastocysts had a 31% reduced probability of being a boy (OR 0.69 (95% CI: 0.60; 0.80)). LIMITATIONS, REASONS FOR CAUTION: It is possible that some residual confounding remains. WIDER IMPLICATIONS OF THE FINDINGS: Blastocyst selection during ART does not appear to introduce any negative effects on obstetric outcome. Therefore, clinicians and patients can be reassured that the assessment scores of the selected blastocyst will not in themselves pose a risk of preterm birth or affect birthweight and the length at birth. STUDY FUNDING/COMPETING INTEREST(S): Unrestricted grant from Gedeon Richter Nordics AB, Sweden. None of the authors have any competing interest to declare. TRIAL REGISTRATION NUMBER: N/A.